If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39 = 5g + -9 Reorder the terms: 39 = -9 + 5g Solving 39 = -9 + 5g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-5g' to each side of the equation. 39 + -5g = -9 + 5g + -5g Combine like terms: 5g + -5g = 0 39 + -5g = -9 + 0 39 + -5g = -9 Add '-39' to each side of the equation. 39 + -39 + -5g = -9 + -39 Combine like terms: 39 + -39 = 0 0 + -5g = -9 + -39 -5g = -9 + -39 Combine like terms: -9 + -39 = -48 -5g = -48 Divide each side by '-5'. g = 9.6 Simplifying g = 9.6
| 3(4x+2)=2(4x+50) | | 1-7x+3=-17 | | 45.3*6= | | 1000=2000*(1+x) | | -12-5+11+4-5-13=12 | | -5c+6=-29 | | 14=-(p-8)+2 | | 6x+3=4x-8 | | 1000=x*(1+0,45) | | 3(3a-5)=60 | | 7(1+4x)=147 | | 4z^2-12z+13=0 | | w-15=4 | | 0=1.5x+x^1 | | -1+(-1.5)= | | 6(2x+5)= | | -3(-4x+2)=18 | | 3(10-3x)=120 | | x+1/4=5/8 | | 10-4x=6x-90 | | 0=16t^2-24t-1 | | x-33/7=2/3 | | 0=16t^2+24t+1 | | -7+4=-35 | | 14-7x=40-21x | | 3(9+6x)=9 | | -19x=57 | | N(t)=25t^3-25t^2+4t+2 | | H=16t^2+24t+1 | | -6n+2=-4n-14 | | 161-4x=23x+17 | | 14=2(x+7)-14 |